Translation and validation of the Urdu version of the European organization for research and treatment of cancer core quality of life questionnaire (EORTC QLQ-C30) and brain module (QLQ-BN20) in primary brain tumor patients - Nida Zahid; Russell Seth Martins; Wajeeha Zahid; Wardah Khalid; Iqbal Azam; Shireen Shehzad Bhamani; Nargis Asad; Khabir Ahmad; Adnan Abdul Jabbar; Muhammad Shahzad Shamim; Rashid Jooma Khan; Gohar Javed; et al. (SpringerOpen, 2021)
Plain language summary Quality of life (QoL) is an important facet of well-being for patients with primary brain tumors (PBTs), as these individuals face significant distress during the course of their illness and treatment. It is important to have valid and reliable tools to accurately measure the QoL of patients with PBTs. The EORTC QLQ-C30 (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire) and its brain tumor-specific module EORTC QLQ-BN20 (EORTC QLQ-Brain Neoplasms 20) are exactly that. However, the use of the EORTC QLQ-C30 and QLQ-BN20 is limited in Pakistan, where the national language is Urdu, and the majority of patients are of low socioeconomic backgrounds. Since no Urdu translations of the EORTC QLQ-C30 and QLQ-BN20 exist, we aimed to translate and validate these tools to enable their applicability in Pakistan. The Urdu versions of the EORTC QLQ-C30 and QLQ-BN20 demonstrated good validity amongst patients with PBTs. Thus, our study confirms the EORTC QLQ-C30 and QLQ-BN20 as valuable clinical tools for the measurement of QoL in primary brain tumors patients within the linguistic, cultural and socioeconomic context of Pakistan.